Approximation of iterative methods for altering points problem with applications - Khan, Aysha; Akram, Mohammad; Dilshad, Mohammad (Mathematical modelling and analysis, 2023)
In this paper, we consider and investigate an altering points problem involving generalized accretive mappings over closed convex subsets of a real uniformly smooth Banach space. Parallel Mann and parallel S-iterative methods are suggested to analyze the approximate solution of altering points problem. Consequently, some systems of generalized variational inclusions and generalized variational inequalities are also explored using the conceptual framework of altering points. Convergence of suggested iterative methods are verified by an illustrative numerical example.